Use of Addition Silicones in the Final Impression of a Fixed Prosthesis - Luz Amelia Granda Macías; Odalys Belén Quishpe Cóndor; Rómulo Guillermo López Torres; Verónica Alejandra Salame Ortiz (Medisur)
Addition silicones are classified as the most widely used materials for dental treatments because they are capable of capturing minute details of the impression, in addition to offering a variety of viscosities to be used in dental practice. This research was carried out with the objective of determining the main theoretical supports available about the use of addition silicones as the material of choice for taking final impressions for the production of a fixed prosthesis. A search of information obtained from databases such as Latindex, Redalyc, Scielo, Medigraphic, Pubmed, Dialnet, of the last 5 years, from 2017 to 2022 was carried out. According to several authors, addition silicone is the material with the best capacity reproduction of details which guarantees success in fixed prosthodontic treatments.